Penanaman Karakter Disiplin Peserta Didik Melalui Program Asrama Di Sekolah - Camellia, Camellia; Sutra Devi, Wayan Helen (Jurnal Civic Hukum, 2024)
Instilling disciplined character is very important for students. Various efforts are made to form a disciplined character in students at school. Some of them are through programs designed for schools that have student dormitories. The researcher aims to explore dormitory programs that are able to instill disciplinary character using a qualitative approach through the case study method. This research was located at SMA Negeri 3 Kayuagung School. The sampling technique used in this research was a purposive sampling technique with 5 informants. The data collection techniques used are documentation, interviews and observation techniques. From the research results, it was found that the dormitory program at SMA Negeri 3 Kayuagung, which includes dormitory picket activities, evening roll call in the dormitory, and eating together in the public kitchen, has gone well in instilling a disciplined character in students, this is indicated by the percentage The average level of discipline of students at SMA Negeri 3 Kayuagung boarding school is 98% with a very good category in terms of 4 aspects of disciplinary character, namely attitude discipline, worship discipline, time discipline, and discipline in enforcing rules.